Late Quaternary Ostracode From a Core in the Weddel Sea, Antartica - WHATLEY, ROBIN; ROBERTS, RAYMOND (Pesquisas em Geociências, 1999)
Fifty-nine samples from a 560cm gravity core of late Quaternary age (PS1003-2), collected at a depth of 2796m in the Weddell Sea, were examined for Ostracoda. The fauna was sparse but, from a total of 556 valves, the rather low diversity fauna of 19 species belonging to 11 genera and 3 families was identified. The study is principally concerned with species diversity, originations and extinctions, inter-relationships between species and the relationship of the fauna to different water masses. With respect to species diversity and origination/extinction patterns, two distinct phases are apparent: an initial diversification (originations only), followed by a phase of overall stable diversity (originations approximately matched by extinctions). The ostracod fauna is closely comparable to that described by authors as typical of North Atlantic Deep Water but is actually from the Antarctic Bottom Water (AABW). Two of the principal constituent species Henryhowella dasyderma (Brady) and H. asperrima (Ruess) seem to be mutually exclusive within the core. Changes in the fauna through the core seem to be related to climatic cycles.